Analisis Motivasi Belajar Mahasiswa pada Pembelajaran Kalkulus Integral Berbasis Maple - Astriyani R. Taneo; Prida N. L. Taneo; Farida Daniel (Publikasi Pendidikan, 2019)
Learning motivation is the process internal to active, guidin and maintaining behaviour from time by time. Calculus integral is one of the subject that important to learn by the students who become a math teacher so need to improve the students learning motivation by improve IPTEK as the tool in teaching and learning process. The purpose of this study is to analyize about learning motivation for students’ to learn calculus integral based on maple. Method that used in this study is qualitative description that conducted at STKIP Soe. The participants of this study are the students who are taking the calculus integral course. The technique that used to collecting the data are observation, questionnaire and interview to analyize the data used Miles and Huberman technique. Test validity data used triangulation technique. The result of this study that learning calculus integral use maple aplication in order to able to improve students’ learning motivation so student more diligent, strengh in find difficuties, uneasy to deliver the answer from the other friends also students like to do the questions out of that given by the lecturer.